2018
DOI: 10.1080/09540121.2018.1549720
|View full text |Cite
|
Sign up to set email alerts
|

Social support, disclosure and stigma and the association with non-adherence in the six months after antiretroviral therapy initiation among a cohort of HIV-positive adults in rural KwaZulu-Natal, South Africa

Abstract: The World Health Organisation (WHO) recommends antiretroviral treatment (ART) initiation at human immunodeficiency virus (HIV) diagnosis. As ART programmes expand, addressing barriers to adherence is vital. Past mixed findings on the association between social support, stigma and non-disclosure with ART adherence highlights the need for further research. The primary aim of this study was to examine how these factors are associated with ART non-adherence in the six months after ART initiation. The secondary aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
(63 reference statements)
3
11
0
Order By: Relevance
“…We found no association between perceived stigma or disclosure of HIV status and adherence to ART among MSM in Indonesia. These results are in line with previous studies [2,38].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found no association between perceived stigma or disclosure of HIV status and adherence to ART among MSM in Indonesia. These results are in line with previous studies [2,38].…”
Section: Discussionsupporting
confidence: 94%
“…Men who have sex with men (MSM) and transgender women are subjected to high levels of human immunodeficiency virus (HIV)-related stigma and often criminalized, affecting access to quality care for sexual health, HIV prevention, and treatment [1,2]. Also, MSM receive stigma, discrimination, judgment, and unfair treatment by health workers in several health services.…”
Section: Introductionmentioning
confidence: 99%
“…Our research also attributed poor adherence to working away from home ( p = 0.011). Various work-related reasons that lead to non-adherence were revealed [ 13 ]. Particularly, the most common causes were due to an intense schedule and fear of stigma at the patients’ workplaces.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were considered non-adherent when they did not meet at least one of those requirements. In terms of factors associated with patients’ non-adherence, prior studies indicated that the most common causes were alcohol consumption, drug and substance abuse, working away from home and lack of good knowledge about ART adherence and family support [ 11 , 12 , 13 ]. Thus, in addition to patients’ knowledge and adherence, our questionnaire also considered the aforementioned factors.…”
Section: Methodsmentioning
confidence: 99%
“…Social support is protective of mental health problems and utilization of health-related services among MSM [42]. Cohort studies showed that better social support predict better adherence to ART and viral suppression [43,44].…”
mentioning
confidence: 99%